2013
DOI: 10.14742/ajet.6
|View full text |Cite
|
Sign up to set email alerts
|

Design of a blended learning environment: Considerations and implementation issues

Abstract: This study identified critical issues in the design of a blended learning environment by examining basic design considerations and implementation issues. Following a designbased research approach with the phenomenological tradition of qualitative research, the study investigated instructor experiences relating to the design, development, and implementation processes of a blended course. The results reveal that the design considerations centred on the pedagogical approach, course organization, materials prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 37 publications
5
76
0
1
Order By: Relevance
“…First, learners' prior knowledge was measured by completing (online) tests, (Alonso et al, 2005;Carman, 2005;McKenzie et al, 2013), answering questions related to that week's learning objectives (Cooner, 2010), or an assessment during an introductory face-to-face meeting (Alonso et al, 2005). Second, in order to provide students with organizational information, 10 studies reported about the implementation of an introductory face-to-face meeting to communicate learning objectives, tasks to be completed, and course material (Alonso et al, 2005;Antonoglou, Charistos, & Sigalas, 2011;Cooner, 2010;Derntl & Motschnig-Pitrik, 2005;Gedik, Kiraz, & Ozden, 2013;HoicBozic et al, 2009;Karoğlu, Kiraz, & Ozden, 2014;Kerres & De Witt, 2003;Köse, 2010;Martyn, 2005).…”
Section: Orienting and Planningmentioning
confidence: 99%
See 4 more Smart Citations
“…First, learners' prior knowledge was measured by completing (online) tests, (Alonso et al, 2005;Carman, 2005;McKenzie et al, 2013), answering questions related to that week's learning objectives (Cooner, 2010), or an assessment during an introductory face-to-face meeting (Alonso et al, 2005). Second, in order to provide students with organizational information, 10 studies reported about the implementation of an introductory face-to-face meeting to communicate learning objectives, tasks to be completed, and course material (Alonso et al, 2005;Antonoglou, Charistos, & Sigalas, 2011;Cooner, 2010;Derntl & Motschnig-Pitrik, 2005;Gedik, Kiraz, & Ozden, 2013;HoicBozic et al, 2009;Karoğlu, Kiraz, & Ozden, 2014;Kerres & De Witt, 2003;Köse, 2010;Martyn, 2005).…”
Section: Orienting and Planningmentioning
confidence: 99%
“…Fourth, a frequently occurring activity was the familiarization of learners with the technology used in the online component. In several studies, an introductory face-to-face meeting was organized in order to (a) introduce learners to the technology (Köse, 2010;Martyn, 2005), (b) inform learners about the online tools and features of web 2.0 (Alonso et al, 2005;Antonoglou et al, 2011;Kerres & De Witt, 2003;Köse, 2010), and (c) show learners how to navigate in the learning platform (Antonoglou et al, 2011;Cooner, 2010;Derntl & Motschnig-Pitrik, 2005;Gedik et al, 2013;HoicBozic et al, 2009;Kerres & De Witt, 2003;Martyn, 2005;Olapiriyakul & Scher, 2006). In this respect, Kim et al (2014) mentioned no instructional activities to familiarize learners with used technologies, but argued that instructors need to provide technologies that are familiar to students and easy to access.…”
Section: Orienting and Planningmentioning
confidence: 99%
See 3 more Smart Citations